La religiosidad de los tarascos en voz de sus doctrineros (1540-1640) - Escandón, Patricia (Studi e materiali di storia delle religioni, 2020)
Both the Relación de Michoacán (c.1541) - compiled by fray Jeronimo de Alcala - and some missionary writings from the late 16th and the early 17th centuries collected information on the religiosity of groups living in lands of Michoacan. But while the Relación is a record of belief and ritual among the uacúsecha lineage before the Spanish conquest, the second set of works deals with the faith and liturgical practices of the Christianized local communities, that were called by the generic name "Tarascos", whether or not they descended from the uacúsecha. This paper attempts to propose the potential influence of the ancient uacúsecha rituality on the Christianized Tarascan new liturgical practices and institutions.